ChemInform Abstract: A New Library of 4(3H)‐ and 4, 4′(3H, 3H′)‐Quinazolinones and 2‐(5‐Alkyl‐1, 2, 4‐oxadiazol‐3‐yl)quinazolin‐4(3H)‐one Obtained from Diaminoglyoxime. Issue 44 (14th October 2013) - Moghimi, Abolghasem; Khanmiri, Rahim Hosseinzadeh; Omrani, Ismail; Shaabani, Ahmad
Abstract Acetic acid mediated condensation of diarylaminoglyoxime (I) with anthranilic acids (II) or aminobenzoate (VI) leads to the formation of quinazolinones.